The importance of reputation (online reviews and word of mouth) within Indian restaurants in the UK. - Kansara, Rima (2015)
ABSTRACT This paper explores the importance of reputation (online reviews and word of mouth)for Indian restaurants in the UK. It analyses whether reputation is important, how it is important and the impact it has on the successfulness of Indian restaurants. The study interviews 17 respondents from 14 different restaurants. Additionally, online score ratings and payment histories are used to determine the successfulness of a restaurant. The analysis suggests that reputation is an important factor for the success of an Indian restaurant, however it is not the only factor. Findings show that different variables can also influence the success of an Indian restaurant, and those variables also determine their reputation.